Mechanisms of nuclear protein import - Melchior, Frauke; Gerace, Larry (Current opinion in cell biology, 1995)
The past two years have seen a significant increase in our understanding of nuclear protein import. Five cytosolic import factors have been identified, two of which have been shown to directly interact with components of the nuclear pore complex. These findings enable refinement of previous models for steps in the nuclear import pathway, and provide a framework for future research.
Gesehen am 17.08.2023